Morphological Errors in Main News Headlines Harian Singgalang August–November 2025 Edition - Frisca Dilla (Universitas Indo Global Mandiri, 2026)
Language in mass media plays an important role in shaping public opinion, so that language errors at the morphological level can reduce the quality of the information conveyed. This study aims to identify and analyze morphological errors in the headlines of the Singgalang Daily, published in the August–November 2025 edition. The research method used is a descriptive qualitative method with a reading and note-taking technique. Data analysis techniques include the stages of identification, classification, description, and evaluation of morphological errors, especially in the aspects of affixation, reduplication, and compounding. The results of the study indicate that there are morphological errors with the most dominant language errors being compounding errors, with 20 data points, such as writing compound words that do not comply with EYD V rules. The primary factors contributing to errors are the authors' unfamiliarity with linguistic rules and their tendency to use incorrect forms. These findings conclude that there is a need for increased awareness and linguistic competence for mass media editors to maintain the quality of journalistic language. This research is expected to be a reference for the media in improving the use of Indonesian and contribute to the preservation of good and correct Indonesian in the realm of public communication. Keywords: Language errors, Mass media, Morphology